2001
DOI: 10.1046/j.0953-816x.2001.01820.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory antioxidants attenuate the expression of inducible nitric oxide synthase mediated by advanced glycation endproducts in murine microglia

Abstract: Advanced glycation endproducts (AGEs) accumulate on long-lived protein deposits including beta-amyloid plaques in Alzheimer's disease (AD). AGE-modified amyloid deposits contain oxidized and nitrated proteins as markers of a chronic neuroinflammatory condition and are surrounded by activated microglial and astroglial cells. We show in this study that AGEs increase nitric oxide production by induction of the inducible nitric oxide synthase (iNOS) on the mRNA and protein level in the murine microglial cell line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 50 publications
0
63
0
1
Order By: Relevance
“…Ginkgo biloba also exerts an antiphlogistic effect on inflammatory cells, mostly by suppressing the production of active oxygen and nitrogen species [8]. Furthermore, the flavone component of GBE also inhibits lipid peroxidation reactions and platelet aggregation [15] and enhances antioxidant enzyme activities [20]. The free radical scavenging activity of GBE is comparable to that of other known antioxidants such as vitamins A and C, as well as the tripeptide glutathione peroxidase [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ginkgo biloba also exerts an antiphlogistic effect on inflammatory cells, mostly by suppressing the production of active oxygen and nitrogen species [8]. Furthermore, the flavone component of GBE also inhibits lipid peroxidation reactions and platelet aggregation [15] and enhances antioxidant enzyme activities [20]. The free radical scavenging activity of GBE is comparable to that of other known antioxidants such as vitamins A and C, as well as the tripeptide glutathione peroxidase [15].…”
Section: Discussionmentioning
confidence: 99%
“…Ascorbic acid and superoxide dismutase acting as scavengers of superoxide radicals indirectly preserve activity of NO. GBE can scavenge NO and inhibit its production by NO synthase, reducing the nitrate levels in a dose-dependent manner [15]. In some studies it was found that NO levels increased in untreated rats after myringotomy [1].…”
Section: Discussionmentioning
confidence: 99%
“…iNOS, IL1ß, IL6 and TNF have been detected in amyloid plaques and adjacent microglial and astroglial cells [59]. Activated glia are a further source of ROS (such as superoxide and NO) through the activation of NADPH oxidase and iNOS, respectively [60,61]. ROS act as second messengers in proinflammatory signal transduction and intracellular acting antioxidants such as flavonoids including apigenin and diosmetin can thus act as anti-inflammatory drugs for these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Ras interacts with PI3-kinase, protein kinase C, diacylglycerol kinase, and MAP-kinase-kinase-kinase, regulating expression of IL-1 b, IL-6, and iNOS. LA can scavenge intracellular free radicals (acting as second messengers), downregulate proinflammatory redox-sensitive signal transduction processes including NF-kB translocation, and thus attenuate the release of more free radicals and cytotoxic cytokines (Bierhaus et al 1997;Wong et al 2001a).…”
Section: La: An Anti-inflammatory Antioxidant and Modulator Of Redox-mentioning
confidence: 99%